A typical presentation of myocardial ischaemia as referred pain to jaw in a young adult: a case report - Ariyarathne, D.; Hulathduwa, S.R. (University of Jaffna, 2012)
Ischaemic Heart Disease (IHD) accounts for the highest mortality rate among the non-communicable diseases across the globe. In the developed countries the incidence of IHD shows a slow decline over the past two decades. It is traditionally considered as a disease of the elderly though clinicians and pathologists experience more and more younger individuals getting affected by the condition since last few decades due to varied of reasons. IHD has a variety of presentations some of which could lead to diagnostic difficulties unless due caution is exercised. Isolated referred pain to teeth, jaw or craniofacial region is one such rare presentation for which many theories have been put forward to explain the mechanism though none is conclusive. When a patient complains of an unusual pain in the craniofacial region or the jaw, the remote possibility of its cardiac origin should always be born in the mind of the examining physician or the dental surgeon. Otherwise it could not only lead to unnecessary dental interventions but also it could delay the diagnosis and treatment of a more serious health condition of the patient sometimes leading to severe morbidity or even death. This case illustrates a situation where a young male suffering from intermittent tooth pain/jaw pain for over a period of three months, seeking dental treatment including extractions and restorations from a qualified dental surgeon, suddenly collapsed and died at workplace after complaining of excruciating tooth-pain. The cause of death was established after the meticulous post mortem examination as IHD due to coronary thrombosis.
Keywords: Ischaemic heart disease; Referred pain; Tooth pain; Coronary thrombosis; Maxillofacial